(untitled) (Global Scientific Review, 2022)
the article is devoted to the study of the section of the Russian language. The authors of the article pay attention to speaking in Russian as a type of speech activity, primarily relying on the language as a means of communication. The article provides methodological recommendations for organizing and conducting Russian language classes in national groups in the form of conversations, observations of the language, introducing language forms and constructions into students’ speech based on the awareness of their functions and the rules for their use. Possibilities of using visual and technical means in teaching